2018
DOI: 10.1371/journal.pone.0196556
|View full text |Cite|
|
Sign up to set email alerts
|

Performance of next-generation sequencing on small tumor specimens and/or low tumor content samples using a commercially available platform

Abstract: BackgroundNext generation sequencing tests (NGS) are usually performed on relatively small core biopsy or fine needle aspiration (FNA) samples. Data is limited on what amount of tumor by volume or minimum number of FNA passes are needed to yield sufficient material for running NGS. We sought to identify the amount of tumor for running the PCDx NGS platform.Methods2,723 consecutive tumor tissues of all cancer types were queried and reviewed for inclusion. Information on tumor volume, success of performing NGS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Tissue samples taken for pathological diagnosis, including fresh, frozen and formalin-fixed tissues, are often used for comprehensive cancer genome analysis. Recent technical developments, especially high-throughput sequencing, enables researchers to subject formalin-fixed paraffin-embedded (FFPE) tissues to cancer genome analysis using next generation sequencing (NGS) [14]. A major advantage of FFPE tissues over frozen tissue is that pathologists can observe the cancer lesions in the same region of the samples that is subjected to genome analysis to directly and accurately compare the histological findings and genomic profiles [5].…”
Section: Introductionmentioning
confidence: 99%
“…Tissue samples taken for pathological diagnosis, including fresh, frozen and formalin-fixed tissues, are often used for comprehensive cancer genome analysis. Recent technical developments, especially high-throughput sequencing, enables researchers to subject formalin-fixed paraffin-embedded (FFPE) tissues to cancer genome analysis using next generation sequencing (NGS) [14]. A major advantage of FFPE tissues over frozen tissue is that pathologists can observe the cancer lesions in the same region of the samples that is subjected to genome analysis to directly and accurately compare the histological findings and genomic profiles [5].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive NGS test was performed to analyze actionable gene mutations, copy number variations (CNVs), and mRNA expression by using the Paradigm Cancer Diagnostic's (PCDx) NGS platform according to the previously described methodology [11]. The PCDx test is a clinical-grade targeted NGS test run in a Clinical Laboratory Improvement Amendments–certified and College of American Pathologists–accredited laboratory [12]. The platform measures genomic, transcriptomic, and proteomic aberrations linked with 86 unique therapies based on published patient research information for tumors all cancer types.…”
Section: Methodsmentioning
confidence: 99%
“…The platform measures genomic, transcriptomic, and proteomic aberrations linked with 86 unique therapies based on published patient research information for tumors all cancer types. Accordingly, the PCDx test helps to guide treatment especially for tumor types that have potential targeted therapy options, like breast cancer, colorectal cancer, and NSCLC, but also SCLC, mesothelioma, and gastric cancer [12]. The sequencing was performed by using the Ion 318 chip on the Ion PGM sequencer (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In October 2019, it was granted expanded approval for use in the detection of mutations of EGFR on exons 18 to 21 5 . However, NGS‐based companion diagnostics sometimes fail to analyze gene alterations because of the insufficient quantity or quality of specimens; failure caused by insufficient quantity has been previously reported in 6.4% to 33.8% of cases 6,7,8 . Although an improvement of the analysis success rate is needed in this setting, few studies have reported on the specimens that are suitable for NGS‐based companion diagnostics, including ODxTT.…”
Section: Introductionmentioning
confidence: 99%